Genetika shizofrenije - Kores-Plesničar, Blanka (Medicinski razgledi, 1999)
The authors give a brief description of schizophrenia based on the establishedinternational criteria, and discuss its epidemiology and aetiology.They present family, twin and adoption studies wich have reinforced the role of genetic factors in the aetiology of schizophrenia. Next they discuss various inheritance patterns, the hypothesis of the site of a single gene locus for schizophrenia and role of non-genetics factors. Recent studies aimed at detecting and localizing the dominant gene linked to schizophrenia ona locus of chromosome 6 seem most promising, yet evi- dence is accumulating that the mode of inheritance is either polygenic (caused by many genes exerting slight effects), or oligogenic (caused by a few genes exerting moderate effects), with an important role being played by environmental factors. Modern genetic methods will certainly improve our understanding of the aetiology and development of schizophrenia in the foreseeable future.
Keywords: Schizophrenia; shizofrenija; Genetics; genetika; dedovanje; Pedigree; Chromosome abnormalities; geni; Chromosomes, human, pair 5; Chromosomes, human, pair 11; Chromosomes, human, pair 22; X chromosome